Databases in Networked Information Systems 10th International Workshop, DNIS 2015, Aizu, Japan, March 23-25, 2015, Proceedings - Chu, Wanming; Kikuchi, Shinji; Bhalla, Subhash (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2015)
This book constitutes the refereed proceedings of the 10th International Workshop on Databases in Networked Information Systems, DNIS 2015, held in Aizu-Wakamatsu, Japan, March 2015. The 14 revised full papers presented together with 7 invited papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on big data analysis, information and knowledge management, business data analytics and visualization, networked information resources, and business data analytics in astronomy and sciences.